2003
DOI: 10.1002/med.10039
|View full text |Cite
|
Sign up to set email alerts
|

In silico prediction of drug‐binding strengths to human serum albumin

Abstract: Drug binding to Human Serum Albumin (HSA) is an area of intense research. The pharmacokinetics and pharmacodynamics of drugs are strongly affected by their binding to this protein. In this article, the field is reviewed, as well as our models to predict drug-binding affinities to HSA from drug structure. The physiological role of HSA is described, as well as its influence in drug action. The crystal structures of this protein are discussed, emphasizing the two drug-binding sites and the fatty acids binding sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
189
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(202 citation statements)
references
References 51 publications
9
189
0
Order By: Relevance
“…It is also important to have the ability to estimate these in vitro properties from the chemical structure thus helping the design stage of the molecules too. It has been shown that the retention of compounds obtained on the proposed biomimetic stationary phases can be estimated in silico [52][53][54][55], however it is worth noting that the in silico models use 2D molecular descriptors that are not sufficient to estimate the 3D contribution of the molecules binding to proteins, therefore they can be used only as a rough estimations.…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to have the ability to estimate these in vitro properties from the chemical structure thus helping the design stage of the molecules too. It has been shown that the retention of compounds obtained on the proposed biomimetic stationary phases can be estimated in silico [52][53][54][55], however it is worth noting that the in silico models use 2D molecular descriptors that are not sufficient to estimate the 3D contribution of the molecules binding to proteins, therefore they can be used only as a rough estimations.…”
Section: Introductionmentioning
confidence: 99%
“…Three of the seven FA binding sites overlap with the two main drug binding sites, namely FA3 and FA4 overlap with site II, and FA7 with site I [8,12]. Therefore, competition between the drugs and FAs for the same binding sites is possible, although cooperativity, or even lack of competition have been observed in some cases [13].…”
Section: Interaction Of Anticancer Metallodrugs With Proteins Is Of Cmentioning
confidence: 99%
“…This would allow speeding up of the design of new compounds with appropriate BSA binding properties and therefore the optimization of the pharmacokinetics. This approach has been successfully utilized for the prediction of many physical properties, and it is one of the main approaches in the area of binding affinity prediction [18][19][20]. To the best of our knowledge, there are no QSPR studies focused on the prediction of the binding constants of active traditional Chinese medicine constituents measured by fluorescence quenching until now.…”
Section: Central European Journal Of Chemistrymentioning
confidence: 99%